Effectiveness of Secondary Metabolites from Entomopathogenic Fungi for Control Nilaparvata lugens Stål. in the Laboratory Scale - Endang Warih Minarni; Loekas Soesanto; Agus Suyanto; Rostaman Rostaman (Jurnal Perlindungan Tanaman Indonesia, 2021)
Nilaparvata lugens Stål. is an essential pest in rice plants. This pest attack can reduce crop yields and even crop failure. This research was conducted to obtain secondary metabolites that are effective in controlling brown planthopper (BPH). A randomized block design was used to test the effectiveness of secondary metabolites against BPH. The treatments tested were secondary metabolites produced by eight isolates of fungi consist of three concentrations: 5, 10, and 15%. Water and imidacloprid insecticide were used as control. The eight isolates were: J11 (Aspergillus sp.), J22 (Lecanicillium saksenae), J34 (Myrothecium sp.), J35 (Beauveria sp.), J41 (Fusarium sp.), J56 (Fusarium sp), J60 (Simplicillium sp.), and J65 (Curvularia sp.). Each treatment was repeated three times. The variables observed were mortality and time of death of BPH. Data were analyzed using the F test and followed by a DMRT if significant differences existed. The results showed that the secondary metabolites of the Lecanicillium saksenae, Myrothecium sp., and Simplicillium sp. fungi effectively controlled BPH pests by 80‒100% within 3.22‒5.47 days. The fungus L. saksenae, Myrothecium sp., and Simplicillium sp. contain insecticidal compounds, clogging the insect spiraculum, antifeedant, repellant, and antimicrobial.